Comparative epidemiology and control of trypanosomes - Murray, M.; Trail, J.C.M. (Australian Academy of Science, 1986)
Trypanosomiasis in man and domestic animals in Africa is discussed with particular reference to the complexity and economics of the disease and the effectiveness of current methods of control.